Development of a conceptual model for the ultra-fine particulate matter processes in gasoline direct injection engines using integrated CFD-chemical kinetic modelling - Tan, Jing Yang (2020)
Despite the improvement in fuel economy and engine performance, gasoline direct injection (GDI) engines have been relatively recently identified as a prominent source of ultra-fine particulate matter (PM) which mainly consists of soot. Adverse health impacts of these airborne particles call for stringent legislations to monitor both the number and mass emissions. Set against this background, an integrated computational fluid dynamics (CFD)-chemical kinetic modelling approach is developed in order to acquire an in-depth understanding of PM processes within GDI engine configurations.